2020
DOI: 10.3892/ijmm.2020.4594
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of liver regeneration and anti‑fibrotic effects of the TGF‑β receptor kinase inhibitor galunisertib in CCl4‑treated mice

Abstract: The cytokine transforming growth factor-β (TGF-β) serves a key role in hepatic fibrosis and has cytostatic effects on hepatocytes. The present study investigated the anti-fibrogenic and regenerative effects of the TGF-β receptor type I kinase inhibitor galunisertib (LY2157299) in mice with carbon tetrachloride (CCl 4 )-induced liver cirrhosis and in vitro. Mice were intraperitoneally treated with CCl 4 for 8 weeks. At week 5, the mice were divided randomly into four treatment groups: Vehicle-treated; and treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Galunisertib is a highly selective inhibitor of TGFβR1 that has been demonstrated to completely inhibit phosphorylation and activation of SMAD2/3 [89]. Although the anti-fibrotic properties of galunisertib have not been widely explored, there is an emerging evidence for its therapeutic efficacy in liver fibrosis [26,27]. To date, the only report showing a potential benefit of galunisertib for the treatment of renal fibrosis in vivo is the study by Ding et al [90].…”
Section: Galunisertibmentioning
confidence: 99%
“…Galunisertib is a highly selective inhibitor of TGFβR1 that has been demonstrated to completely inhibit phosphorylation and activation of SMAD2/3 [89]. Although the anti-fibrotic properties of galunisertib have not been widely explored, there is an emerging evidence for its therapeutic efficacy in liver fibrosis [26,27]. To date, the only report showing a potential benefit of galunisertib for the treatment of renal fibrosis in vivo is the study by Ding et al [90].…”
Section: Galunisertibmentioning
confidence: 99%
“…In addition, we found that TGF-β was increased in AR113+ PHx group at day 7 after PHx. TGF-β is produced principally in the hepatic stellate cells, and is a representative mitoinhibitory factor, which presumably induces the termination of liver regeneration (Masuda et al, 2020). Our study showed that whether probiotics are given before or after PHx will affect the expression of cytokine expression level.…”
Section: Discussionmentioning
confidence: 61%
“…We acknowledge that various TGF‐β receptor inhibitors (both antibody and small molecule) have various efficacies, benefits, and limitations. GAL dose schedules may be a limiting factor, as high doses of GAL are known to cause toxicity in animal models 51,52 . It is unlikely that GAL per se will be used in clinical trials but multiple other studies combining anti‐TGF‐β based therapy with immunotherapy are under investigation (http://clinicaltrials.gov) demonstrating value in this approach.…”
Section: Discussionmentioning
confidence: 99%